Analogue of Electromagnetically Induced Transparency in an S-Shaped All-Dielectric Metasurface - Jinyan Diao; Bingxin Han; Jie Yin; Xiangjun Li; Tingting Lang; Zhi Hong (IEEE Photonics Journal, 2019)
We proposed and numerically investigated an analogue of electromagnetically induced transparency (EIT) all-dielectric metasurface that features one asymmetric S-shaped silicon resonator in the unit cell and generates high transparency, high Q-factor resonance in the near infrared spectral region. Breaking the symmetry of the S-shaped structure could provide a pathway to excite a trapped magnetic mode that coupled to a bright electric dipolar moment, achieving a sharp EIT-like response. And the Q value of the resonance can be easily modified by altering the asymmetric degree of the structure. In particular, the transparency window will almost maintain its symmetric shape and high transmission of 97%, but shift accordingly as the structural parameters (silicon bar's length, width, or thickness) vary in a large range, because of the very small detuning between the two coupled modes. The proposed S-shaped all-dielectric metasurface could ease fabrication challenges and have potential applications in biochemical sensing, narrowband filters, optical modulations, and slow light devices.